PEMBUATAN BAHAN AJAR FISIKA BERBASIS ICT MENGINTEGRASIKAN MSTBK PADA MATERI MEKANIKA KLASIK SISTEM KONTINU UNTUK MENCAPAI KOMPETENSI SISWA SMA KELAS XI - Aufi Husni; Akmam Akmam; Asrizal Asrizal (Universitas Negeri Padang, 2015)
Implementation of Physics learning needs a learning material to support the goal achievement of Physics learning. An alternative solution to achievement the goal of Physics learning is apply the Physics learning materials based ICT by integrating Mathematic, Sciences, technology, disaster, and character values (MSTDC) in the learning of Physics. The purpose of this research is to generate Physics learning material that good description, validity, practicality, and effectivity. Type of this research is the Reserch and Development (R & D). Object of this research is physics learning materials based ICT by integrating MSTDC on classical mechanics especially at continuous system. The instrument for collecting data in this research is validation sheet, practicality sheet, learning outcomes test sheet, and observation sheet. There are two result of the data analysis. First, this learning material is valid with average value 87,50 by expert and 88,03 by practitioners. Design of learning material consists of home, identity learning materials, introduction, learning materials, exercises, evaluation, reference, download, chat, and discussion forums. Second, Physics learning material based ICT by integrating MSTDC is practice and effective are used in physics learning process